The impact of robots on workplace injuries and deaths: Empirical evidence from Europe - Marco De Simone; Dario Guarascio; Jelena Reljic (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
This paper examines the impact of robotisation on workplace safety in EU manufacturing sectors between 2011 and 2019. To address endogeneity concerns, we employ an instrumental variable approach and find that robot adoption reduces both injuries and fatalities. Specifically, a 10% increase in robot adoption is associated with a 0.066% reduction in fatalities and a 1.96% decrease in injuries. Our findings highlight the context-dependent nature of these effects. The safety benefits of robotisation materialise only in high-tech sectors and in countries where industrial relations provide strong worker protections. In contrast, in traditional industries and countries with weaker institutional frameworks, these benefits remain largely unrealised. The results are robust to several sensitivity tests.
Keywords: J01; J08; J28; J50; J81; L60; O33; 330; EU; robotisation; technology; workplace safety; injuries; fatalities; industrial relations